(3cJGH aj GdadSaIs
(3ChdgG (B:s
(3GdMeO ddg ajGV GdYhGQa hSdge MbGFb GdeYGQa hHYO aEf GdYdhe Ydi JTYjH afhfgG Yde GdefWb CMSfgG KHGJkG s
(3BNQgG (B:s
(3Cf fPcQ ajgeG NhGU eJYOOI Ch CMOjgG hdfbJUQ Ydi gPG GdbOQ ef GdcdGe ai bSe GdJUhQGJ MGeOjf deajV GdceGdGJ Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs